Toward a New Measure for Faith and Civic Engagement: Exploring the Structure of the FACE Scale - Droege, Jocelyn R. (Christian higher education, 2012)
Civic and political engagement may encourage individuals to make positive societal contributions and thus act as responsible and productive citizens. A positive relationship between civic/political engagement and the extent of one's faith-based beliefs and behaviors has been the basis for a growing field of research (e.g., Becker & Dhingra, 2001; Chickering, 2006; Dalton, 2006, King, 2008; Uslaner, 2002). Higher education programs that encourage students’ exploration and expression of faith/spirituality may promote a favorable attitude concerning civic engagement (Chickering, 2006). Two studies addressed the relationship between civic/political engagement and faith-based perceptions and behaviors among university students (Study 1: n = 762; Study 2: n = 955). Study 1 ran an exploratory factor analysis on a 20-item Faith and Civic Engagement (FACE) scale and Study 2 replicated the factor structure through confirmatory factor analysis. Results identified five reliable and valid subscales: civic engagement, faith life, political importance, (target university) influences spiritual growth, and (target university) influences personal growth.